Dental Caries Frequency & its Determinants among Adults of District Kohat & Nowshera Khyber Pakhtunkhwa Pakistan - Muhammad Jibran Khan, Mehwish Saba Waheed, Nadia Khan, Muhammad Ishtiaq, Anwar Khan Wazir, Naeemullah, Arif Iqbal, Said Akbar Khan, Jawad Ali, Muhammad Fawad Shirazi (Pakistan Journal of Medical & Health Sciences, 2022)
The objective of this study was to assess the frequency and risk factors of dental caries among adults in District Kohat and Nowshera Khyber Pakhtunkhwa Pakistan. Methods: After taking ethical approval, a descriptive cross sectional study was conducted in District Kohat and Nowshera, in which a total of n=435 adults were assessed and examined for dental caries, from November 2021 to March 2022. A structured questionnaire was used to collect data regarding dental caries and its risk factors. Moreover, relevant tooth brushing, and dietary information was also collected. Data was analyzed by SPSS and results were presented in form of tables. Results: The results showed that 23.68% of adults had dental caries. Approximately, 57.70% of adults are of age between 30-60 years; 25.06% had monthly income less than 25000/PKR per month; 14.02% were illiterate, and 40.92% were overweight and obese. Moreover, 52.64% had compliance to daily tooth-brushing; 49.66% used fluoride tooth paste; 41.15% and 58.85% prefer sugar and sweet beverages respectively. Furthermore, 21.84% had poor oral hygiene; 14.94% had routine dental examinations; and 49.21% & 32.41% prefer vegetables and fruits. Conclusions: Concluded that dental caries showed moderate prevalence among adults and revealed relationship with age; monthly income, body mass index, and literacy level. Moreover, frequency of tooth-brushing, fluoride tooth-paste, oral hygiene status and sweet preference showed association with dental caries and thus comprehensive preventive and health promotion strategies were needed to overcome dental caries among adults.